Analysis of the Implementation of the K3 Management System on Employee Productivity in Private Hospitals in Maluku - Latuconsina, Nur Aisah; Liklikwatil, Nelma (Indonesian Journal of Global Health Research, 2024)
Hospitals as a service industry have a variety of complex workforce problems with various risks. The K3 management system is one of the supporting factors for productivity including policy, commitment, planning, implementation, evaluation and review. If all K3 management systems are implemented well, the company can guarantee the health and safety of workers so that workers feel safer and more comfortable when doing their work. Objective: to analyze the implementation of the K3 management system in hospitals at three private hospitals in Maluku. Method: This research uses Observational Analytical Type with Cross Sectional Study. The research was conducted at 3 private hospitals in Maluku, namely RS. Kindergarten. II Prof. Dr. J.A. Latumeten, RS. Source of Life GPM and RS. Al-Fatah. Sample collection in this study used purposive sampling of 150 respondents, all of whom were related to the implementation of services at the hospital. To determine the relationship between more than one dependent variable, the logistic regression test is used. Results: K3 management system test results with employee work productivity obtained a value of p = 0.019. The results of the analysis of the relationship between K3 commitment and policy and work productivity obtained a p value = 0.015. The results of the K3 planning analysis with work productivity obtained a p value = 0.043. The results of the analysis of K3 implementation with work productivity obtained a p value = 0.045. The results of multivariate analysis using the logistic regression test show that the sig value of 0.034 is a very significant variable on employee work productivity. Conclusion: the conclusion of this research is that there is a relationship between the K3 management system, K3 commitment and policy, K3 planning, K3 implementation and work productivity. The results of the multivariate analysis state that K3 implementation is a variable with a strong influence on employee work productivity.